In Vitro Evaluation of Concentrate Mixtures Containing Incremental Level of Rice Dried Distillers Grain with Solubles Replacing Oil Cakes in Concentrate Mixture - Yogi, R. K.; Thakur, S. S.; Mohini, Madhu; Singh, S. K.; Malik, Tariq (Indian Journal of Animal Nutrition, 2017)
Oil cakes of concentrate mixture (% parts: maize 22, barley 16, wheat bran 15, deoiled rice bran 15, groundnut cake 25, mustard oil cake 10, mineral mixture 2 and common salt 1) in control group were replaced by rice dried diets distillers grains with solubles (RDDGS) at the levels of 25, 50, 75 and 100% on nitrogen basis. About 200 mg of each air-equilibrated samples of concentrate mixtures were evaluated by using in vitro gas production technique. Concentration of NH3-N, total volatile fatty acids and proportion of propionate at the expense of acetate and butyrate was decreased (P<0.01) with inclusion of RDDGS in concentrate. A linear decrease (P<0.01) in methanogensis was observed with incremental level of RDDGS in concentrate. In vitro true dry matter digestibility, decreased (P<0.01) at levels greater than 50% substitution of oil cakes, however, in vitro true OM digestibility was not affected up to 75% inclusion of RDDGS. Partitioning factor and microbial biomass production were higher (P<0.01) with inclusion of DDGS at 75% level. Thus, it could be observed that partial replacement of oil cakes with RDDGS in concentrate did not have any detrimental effect on in vitro rumen fermentation profile whereas the methane production was decreased.